Food-induced Ileus Caused by “KINPIRA-GOBO” - Katami, Atsuo; Kojima, Yutaka; Ishibiki, Yoshiro; Yaginuma, Yukihiro; Hashiguchi, Tadasuke; Sakurada, Mutsumi; Kunii, Yasuhiro; Kihara, Akira (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2003)
A 34-year-old female presented in the outpatient clinic with a chief complaint of abdominal pain and vomiting. A scout film examination of the abdomen and CT scan revealed a markedly expanded small intestine with a full lumen. A diagnosis of strangulated ileus secondary to postoperative adhesion was made, and emergency surgery was performed. A mass was found about 30 cm proxinal to the end of the ileum, and dilatation of the intestinal tract was observed proxinel to the tumor. A small incision in that region revealed a mass of “KINPIRA-GOBO (burdock and carrot) ” measuring about 6×3cm. The mass was considered to be responsible for the ileus and was removed to release the ileus.